Simulação computacional por elementos finitos de múltiplas fissuras em sólidos usando técnica de fragmentação da malha - Maedo, Michael Andrade [UNESP] (2015)
The study of the crack process has been a subject of increasing interest over the past few years. The behavior of various materials such as concrete, masonry, rocks, soils and biomaterials, are governed by the effects arising from the formation of cracks. In the context of finite element methods the formation and propagation of cracks in the interior of the finite elements can be described via finite elements with embedded discontinuities or Generalized Finite Element Method (G-FEM). Both methods require techniques to track the crack path during the analysis. These techniques are relatively simple in representing few cracks in 2D analyses but can be very complex and even unsuitable for multiple cracks and for tridimensional problems. The present work aims to use the mesh fragmentation technique to insert special interface elements between regular elements of the mesh. These interface elements represent the failure process in quasi-brittle materials, where the interface is simulated using finite elements with a high aspect ratio. The constitutive model of the interface elements are compatible with the strong discontinuity regime. The methodology is very attractive, because it avoids the necessity of crack tracking schemes. A comprehensive study of the objectivity of the solutions obtained with the proposed methodology was done thoruhg the analysis of different cases, with different meshes, varying the size and orientation of the finit elements. The results indicated that the technique is able to adequately represent the process of cracking, generating structural responses and crack patterns similar to the experimental ones. The use of unstructured meshes are more appropriate since they to not present alignments that may induce crack propagatio trajectories deviating from the correct ones